Outbreak of carbapenem resistant Klebsiella pneumoniae in a neurorehabilitation unit: Genomic epidemiology reveals complex transmission pattern in a tertiary care hospital - Maria Grazia Silvotti; Erika Scaltriti; Luca Bolzoni; Beatrice Zerbi; Gabriella Tocci; Andrea Zappavigna; Gianfranco Lamberti; Federico Donati; Franco Federici; Stefano Pongolini; Giuliana Lo Cascio (Journal of Global Antimicrobial Resistance)
ABSTRACT: Objectives: Infections by carbapenem-resistant Enterobacterales (CRE) in hospitals represent a severe threat but little is known on outbreaks in rehabilitation wards caused by Klebsiella pneumoniae producing Klebsiella pneumoniae Carbapenemase (KPC-Kp). We report an outbreak by KPC-Kp, in a neurorehabilitation unit in Italy, analysed through whole-genome sequencing (WGS) for transmission routes reconstruction to improve management of KPC-Kp infections in rehabilitation units. Methods: We investigated cases and KPC-Kp isolates collected from February to October 2022 from hospital surveillance. Carbapenem resistance was identified with disk diffusion and minimum inhibitory concentration tests, carbapenemase production through immunochromatographic lateral flow assays. All isolates were genotyped through WGS to highlight possible phylogenetic relationships. The most likely transmission networks of KPC-Kp were reconstructed with Bayesian discrete-time stochastic models. Results: Nineteen patients were colonized by KPC-Kp. Two isolates belonged to sporadic sequence types (STs; ST348 and ST219) whereas 9 of 19 and 8 of 19 isolates belonged to ST307 and ST716, respectively. Among the ST307 isolates, we identified two genomically distinct clusters of five and two cases. All ST716 isolates were highly similar. Genotyping and the reconstruction of transmission networks of KPC-Kp based on genomic data identified seven independent introductions into the neurorehabilitation unit rather than a single outbreak as initially hypothesized before genomic investigation. Three of the seven introductions generated chains of secondary infections, whereas the remaining four remained single cases. Conclusions: The outbreak root-causes were identified in temporary staff shortage and insufficient microbiological surveillance. Measures were adopted accordingly and the outbreak ended. The study highlights the critical role of genomic epidemiology in hospital outbreaks. © 2025 The Author(s). Published by Elsevier Ltd on behalf of International Society for Antimicrobial Chemotherapy.